I am stuck on solving the problem below, writing the answers in standard form of a complex number, can you also show how it is worked out, thanks in advance.

(-2 + 5i) (i - 4) =

(-2 + 5i) (i - 4) =

(-2 + 5i) (i - 4)

= -2(i) - 2(-4) + 5i(i) + 5i(-4) {used foil method}

= -2i + 8 + 5i2- 20i {multiplied through}

= 5i2- 22i + 8 {combined like terms}

= 5(-1) - 22i + 8 {i2is -1}

= -5 - 22i + 8 {multiplied 5 by -1}

= 3 - 22i {combined like terms}

- Algebra House

= -2(i) - 2(-4) + 5i(i) + 5i(-4) {used foil method}

= -2i + 8 + 5i2- 20i {multiplied through}

= 5i2- 22i + 8 {combined like terms}

= 5(-1) - 22i + 8 {i2is -1}

= -5 - 22i + 8 {multiplied 5 by -1}

= 3 - 22i {combined like terms}

- Algebra House